Blockchain-based strategy to optimize certified notifications from government entities - Sergio Zabala-Vargas; Yuli Álvarez-Pizarro; Iván Sánchez-Galvis; Karol Rubio-Vásquez (Administrative Sciences, 2024)
Currently, 4.0 technologies have generated important changes in government entities, promoting digital government transformation (DGT). This article addresses the challenge of improving the security, reliability and traceability of communications and certified notifications of state entities, particularly in the case of the Colombian government entity called the Comisión de Regulación de Comunicaciones (CRC). Four important points are presented in this report: (a) Research interest in blockchain and smart contracts has been greatly increasing, evidenced in a literature review conducted in the SCOPUS index; (b) a global reference framework on the use of emerging technologies, as is the case of blockchain, has been developed, as well as the legal and juridical framework in Colombia as a baseline; (c) a multi-criteria decision making framework has been used, resulting in the choice of the Zilliqa platform; and (d) The Tecnotifica™ V1.0 software tool is developed to automate notifications with stakeholders using blockchain. Its effectiveness and acceptance is validated with a technology acceptance level test (TAM). It is concluded that the incorporation of emerging technologies such as blockchain is of a very high interest and relevance in the digital transformation of the state sector in the world.
Keywords: 350; blockchain; business process; digital government transformation; smart contracts